On progress and rate of the peritectic reaction Fo + SiO2 → En in natural andesitic arc magmas. (15th July 2016) - Zellmer, Georg F.; Sakamoto, Naoya; Matsuda, Nozomi; Iizuka, Yoshiyuki; Moebis, Anja; Yurimoto, Hisayoshi
Abstract: Using a high resolution ion microprobe with SCAPS imaging, the peritectic reaction of forsterite + silica to enstatite was studied down to submicron level in a natural andesitic tephra from the Central Plateau of North Island, New Zealand. The fayalitic component of natural olivines is stable in high-silica melts, and therefore the reaction is in fact a two-step progress: 1. Dissolution of Mg-rich olivine, rate-limited by Fe–Mg interdiffusion at the crystal rim, results in enrichment of Fe in the crystal rim and of Mg in the c . 1 μm wide melt boundary layer around the crystal. 2. Magnesian pyroxenes preferentially but not exclusively nucleate in the melt boundary layer and grow; as soon as these microlites touch the rim of the dissolving olivine, they shield the crystals from the silica-rich melt, thereby preventing further olivine dissolution. At this point, Fe–Mg interdiffusion begins to destroy the Fe-enrichment of the olivine rim. The reaction is completed when the dissolving olivine crystal is completely mantled by magnesian pyroxene microlites. Thick pyroxene mantles are likely the result of pyroxene overgrowth rather than due to peritectic transformation. The morphology of the olivine rim preserves information about the reaction history of the grain. Modeling of Fe–Mg interdiffusion in the olivine rim following its shielding from the melt by pyroxene overgrowth may yield the rates of olivine dissolution and the rates of pyroxene growth if temperature is known. For the tephra we have studied, microlite thermometry yields a temperature of 1137 (±41) °C, indicating an olivine dissolution rate of 3–6 × 10 −11 ms −1 and an initially volumetric pyroxene growth rate of 2.2–5.6 × 10 −21 m 3 s −1 . This points to timescales between olivine crystal uptake into the SiO2 -rich melt and explosive eruption at the surface of a few hours to at most a day.